Effects of long-term climate trends on the methane and CO2 exchange processes of Toolik Lake, Alaska - Eugster, Werner; DelSontro, Tonya; Laundre, James A.; Dobkowski, Jason; Shaver, Gaius R.; Kling, George W. (Frontiers in Environmental Science, 2022)
Methane and carbon dioxide effluxes from aquatic systems in the Arctic will affect and likely amplify global change. As permafrost thaws in a warming world, more dissolved organic carbon (DOC) and greenhouse gases are produced and move from soils to surface waters where the DOC can be oxidized to CO2 and also released to the atmosphere. Our main study objective is to measure the release of carbon to the atmosphere via effluxes of methane (CH4) and carbon dioxide (CO2) from Toolik Lake, a deep, dimictic, low-arctic lake in northern Alaska. By combining direct eddy covariance flux measurements with continuous gas pressure measurements in the lake surface waters, we quantified the k600 piston velocity that controls gas flux across the air–water interface. Our measured k values for CH4 and CO2 were substantially above predictions from several models at low to moderate wind speeds, and only converged on model predictions at the highest wind speeds. We attribute this higher flux at low wind speeds to effects on water-side turbulence resulting from how the surrounding tundra vegetation and topography increase atmospheric turbulence considerably in this lake, above the level observed over large ocean surfaces. We combine this process-level understanding of gas exchange with the trends of a climate-relevant long-term (30+ years) meteorological data set at Toolik Lake to examine short-term variations (2015 ice-free season) and interannual variability (2010–2015 ice-free seasons) of CH4 and CO2 fluxes. We argue that the biological processing of DOC substrate that becomes available for decomposition as the tundra soil warms is important for understanding future trends in aquatic gas fluxes, whereas the variability and long-term trends of the physical and meteorological variables primarily affect the timing of when higher or lower than average fluxes are observed. We see no evidence suggesting that a tipping point will be reached soon to change the status of the aquatic system from gas source to sink. We estimate that changes in CH4 and CO2 fluxes will be constrained with a range of +30% and –10% of their current values over the next 30 years.